Understanding the use of digital technologies to provide disability services remotely during the COVID-19 pandemic; a multiple case study design - Jennifer Fortune; Manjula Manikandan; Sarah Harrington; Owen Hensey; Claire Kerr; Sebastian Koppe; Thilo Kroll; Grace Lavelle; Siobhán Long; Malcolm MacLachlan; Denis Nolan; Meriel Norris; et al. (BMC Health Services Research, 2024)
Abstract Background Using digital technologies to provide services and supports remotely may improve efficiency and accessibility of healthcare, and support people with disabilities to live independently. This study aimed to explore the experience of using digital technologies to access and provide disability services and supports during the Covid-19 pandemic, from the perspective of people with disabilities, families and service providers. Methods Using a multiple case study design, we purposively sampled three cases based on service user characteristics and geographical reach of the service. We conducted semi-structured interviews with 40 service users and service providers. Topic guides and analysis were informed by the Consolidated Framework for Implementation Research (CFIR). Analysis followed a largely deductive approach, using the CFIR constructs as a coding framework. A summary memo was developed for each case. Influence and strength of each construct was rated to identify constructs that influenced implementation of digital technologies. Ratings were compared across services to identify facilitators and barriers to implementation. Results Service users and providers were positive about using digital technologies to access and provide disability services and supports remotely. Advantages over in-person delivery included reduced travel time, increased opportunity for peer support and peer learning, more choice and opportunity to participate in activities, and an enhanced sense of self while accessing services from the secure environment of their home. The urgency to identify new modes of service delivery to meet the needs of service users during Covid-19 was a strong facilitator but did not necessarily result in successful implementation. Other factors that were strong facilitators were the use of adaptations to enable service users to access the online service, service users’ willingness to try the online service, service users’ persistence when they encountered challenges, and the significant time and effort that service providers made to support service users to participate in the online service. Barriers to implementation included the complexity of accessing online platforms, poor design quality of online platforms, and organisations prioritising in-person delivery over online services. Conclusions These findings may allow service providers to leverage facilitators that support implementation of online disability services and supports.